2009
DOI: 10.1080/00071660903247182
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and intestinal histology in broiler chickens fed with dietary chitosan

Abstract: 1. The effect of a low dietary chitosan content (06 g/kg) on growth performance, carcase quality, visceral organs and intestinal morphology was studied. 2. A total of 24 male Marshall Chunky broiler chicks were fed on a commercial basal diet with 0 (control) and 06 g/kg chitosan until 7 weeks of age. Body weight gain and feed intake were higher in the chitosan group but there were no differences in feed efficiency and breast meat, drumsticks and visceral organ weights. 3. There were no difference in intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 20 publications
2
25
0
1
Order By: Relevance
“…Although positive effects have been reported on poultry consuming chitosan or buckwheat alone (Hirano et al, 1990;Razdan & Pettersson, 1994;Kondo & Osad 1996;Tanaka et al, 1997;Mei 2011), this is the first report on positive lipid profile-changing effects of buckwheat with trace amounts of chitosan. Several animal studies have confirmed that supplementing chitosan at up to 50 g/kg in feed has no negative effects on the growth and feed intake of the treated animals (Kobayashi et al, 2002;2006;Han et al, 2007;Hossain & Blair, 2007;Khambualai et al, 2009;Yan & Kim, 2011). Results in the present study agree with those findings as no detrimental effects of chitosan at up to 500 mg/kg were recorded.…”
Section: Discussionsupporting
confidence: 83%
“…Although positive effects have been reported on poultry consuming chitosan or buckwheat alone (Hirano et al, 1990;Razdan & Pettersson, 1994;Kondo & Osad 1996;Tanaka et al, 1997;Mei 2011), this is the first report on positive lipid profile-changing effects of buckwheat with trace amounts of chitosan. Several animal studies have confirmed that supplementing chitosan at up to 50 g/kg in feed has no negative effects on the growth and feed intake of the treated animals (Kobayashi et al, 2002;2006;Han et al, 2007;Hossain & Blair, 2007;Khambualai et al, 2009;Yan & Kim, 2011). Results in the present study agree with those findings as no detrimental effects of chitosan at up to 500 mg/kg were recorded.…”
Section: Discussionsupporting
confidence: 83%
“…Broiler chickens supplemented with either 0.5 or 1.0 g/kg chitosan in diet tended to have better growth and feed conversion efficiency since chitosan probably played a vital role in regulating intestinal microflora including enhancing digestion and absorption of protein (Shi et al 2005). However, male Marshall Chunky broilers fed with 0.6 g/kg chitosan for 7 weeks of age could improve BWG and feed intake but had no difference in feed efficiency (Khambualai et al 2009). It should be noted that the results of growth performance in broiler chickens from several studies were different, possibly owing to a variety of chitosan characteristics such as concentration, degree of acetylation and molecular weight (Goy et al 2009;Khambualai et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, male Marshall Chunky broilers fed with 0.6 g/kg chitosan for 7 weeks of age could improve BWG and feed intake but had no difference in feed efficiency (Khambualai et al 2009). It should be noted that the results of growth performance in broiler chickens from several studies were different, possibly owing to a variety of chitosan characteristics such as concentration, degree of acetylation and molecular weight (Goy et al 2009;Khambualai et al 2009). The highest mortality rate of chicks in group 3 during finisher period may be due to high temperature (30 C) and relative humidity (80%) chito-oligosaccharide (COS) at 0.4% level had higher WBC number than other groups at 42 d of age.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies in broilers indicated that dietary chitosan treatment groups could gain superior performance and feed conversion ratio than the control group (Suk, 2004;Khambualai et al, 2008Khambualai et al, , 2009). Tang et al (2005) also reported that chitosan could improve the growth performance and feed efficiency of piglets.…”
Section: Discussionmentioning
confidence: 99%